2018
DOI: 10.1021/acs.jpclett.8b01999
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation-Induced Topological Phase Transition in Monolayer 1T′-WTe2

Abstract: Monolayer (ML) tungsten ditelluride (WTe) is a well-known quantum spin Hall (QSH) insulator with topologically protected gapless edge states, thus promising dissipationless electronic devices. However, experimental findings exhibit the fast oxidation of ML WTe in ambient conditions. To reveal the changes of topological properties of WTe arising from oxidation, we systematically study the surface oxidation reaction of ML 1T'-WTe using first-principles calculations. The calculated results indicate that the fast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 47 publications
0
26
0
Order By: Relevance
“…A very recent study further demonstrated the out-of-plane switchable polarization in two- or three-layer WTe 2 , although WTe 2 is well-known as a topological semimetal in previous reports. Despite the polarization that was almost negligible compared with traditional perovskite FE (3 orders of magnitude lower than BaTiO 3 ), the Curie temperature amazingly turned out to be around 350 K. The origin of such FE is still unclarified, as the vertical polarization seems to be switchable without vertical ion displacement. It was supposed in this report that the FE may origin from the electron–hole correlation rather than lattice instability, where a relative motion of the electron cloud relative to the ion core may take place .…”
mentioning
confidence: 96%
“…A very recent study further demonstrated the out-of-plane switchable polarization in two- or three-layer WTe 2 , although WTe 2 is well-known as a topological semimetal in previous reports. Despite the polarization that was almost negligible compared with traditional perovskite FE (3 orders of magnitude lower than BaTiO 3 ), the Curie temperature amazingly turned out to be around 350 K. The origin of such FE is still unclarified, as the vertical polarization seems to be switchable without vertical ion displacement. It was supposed in this report that the FE may origin from the electron–hole correlation rather than lattice instability, where a relative motion of the electron cloud relative to the ion core may take place .…”
mentioning
confidence: 96%
“…24 Particularly, 1T′-WTe 2 is even more stable than the 2H phase. 25 Various methods have been applied to tune the transition barrier between these three phases to satisfy diverse needs in multiple devices. For example, Wang et al systematically investigated the electro-chemical dynamic process of MoS 2 nanosheets upon lithium intercalation by in situ high-resolution transmission electron microscopy.…”
Section: Introductionmentioning
confidence: 99%
“…According to XPS measurements, 22,23,26−28 the oxidation driving force are formation of WO x and TeO x on the surface of WTe 2 . Theoretical calculation 24,29 claimed the fast oxidation happens with the aid of H 2 O, which can decrease the reaction barrier. And charge depletion was found to near the O adsorption site, which may induce charge dipolar and even polarization.…”
Section: Introductionmentioning
confidence: 99%